2019
DOI: 10.1002/hbm.24618
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐target attention and visual short‐term memory capacity are closely linked in the intraparietal sulcus

Abstract: The existing literature suggests a critical role for both the right intraparietal sulcus (IPS) and the right temporo‐parietal junction (TPJ) in our ability to attend to multiple simultaneously‐presented lateralized targets (multi‐target attention), and the failure of this ability in extinction patients. Currently, however, the precise role of each of these areas in multi‐target attention is unclear. In this study, we combined the theory of visual attention (TVA) with functional magnetic resonance imaging (fMRI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 69 publications
(222 reference statements)
1
24
0
Order By: Relevance
“…One possibility is that the high blood lactate levels, induced by the exercise, may affect some areas of the cortex and not others. In this way, functions supported by the prefrontal cortex, as processing speed [26], cognitive flexibility [34], and resistance to interference [12] seem to be affected, while those supported by more posterior cortical areas, such as visual attention [22] and task switching [29], are not.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that the high blood lactate levels, induced by the exercise, may affect some areas of the cortex and not others. In this way, functions supported by the prefrontal cortex, as processing speed [26], cognitive flexibility [34], and resistance to interference [12] seem to be affected, while those supported by more posterior cortical areas, such as visual attention [22] and task switching [29], are not.…”
Section: )mentioning
confidence: 99%
“…The effects of acute physical exercise on the cognitive performances of an adult individual are still under discussion [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The existing literature tends to highlight a positive relationship if the exercise is of sub-maximal intensity, while the effects seem to be negative for exhaustive exercises [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Visual working memory (VWM) may seem like an odd choice to measure attention, especially when we are trying to distinguish between attention and working memory functions. However, VWM is a distinct, modality-specific memory store (Fougnie & Marois, 2011 ), and is tightly linked to selective attention, in that both encoding (Emrich et al, 2017 ; Praß & de Haan, 2019 ) and maintenance in VWM require visual attention (Makovski et al, 2008 ; Roper & Vecera, 2014 ; Sandry & Ricker, 2020 ). Huang et al ( 2012 ) used a Visual Short-Term Memory task requiring participants to memorize an array of six colors and then recreate this array from memory after it offset (i.e., full report paradigm).…”
Section: Introductionmentioning
confidence: 99%
“…Although a large number of studies have used online rTMS to target the parietal cortex, few studies have used offline rTMS, which is believed to induce longer lasting effects than does online rTMS. Thus far, only two studies (Morgan, Jackson, Van Koningsbruggen, Shapiro, & Linden, 2013; Praß & de Haan, 2019) have examined the effect of parietal offline‐rTMS on WM. Both reported that offline‐rTMS using continuous theta‐burst stimulation (cTBS) (5 Hz bursts with each burst containing three pulses at 50 Hz) had harmful effects on WM (Morgan et al, 2013; Praß & de Haan, 2019).…”
Section: Introductionmentioning
confidence: 99%